Comparison of control methods for inverted 2-degree of freedom pendulum mounted on the cart; IOP Conference Series: Materials Science and Engineering; Vol. 1118 : Mechanical Engineering and Modern Technologies (MEMT 2020) - Sumenkov O. Y. (2021, 2021)
Title screen